Network Pharmacology and Experimental Validation to Explore the Molecular Mechanisms of Compound Huangbai Liquid for the Treatment of Acne - Di H; Liu H; Xu S; Yi N; Wei G (Dove Medical Press, 2023)
Huifeng Di, Hui Liu, Shuna Xu, Na Yi, Guangchen Wei Jinan City People's Hospital, Jinan, 271100, People's Republic of ChinaCorrespondence: Guangchen Wei, Department of Pharmacy, Jinan City People's Hospital, 001 Xuehu Street, Jinan, 271100, People's Republic of China, Email wgc0088@126.comBackground: Acne is a highly prevalent skin disease, and inflammation plays an important role. Compound Huangbai Liquid (CHL) is a classical traditional Chinese medicine (TCM) with remarkable clinical therapeutic effects on acne. However, a holistic network pharmacological approach to explain the mechanism of CHL in the treatment of acne has not been explored.Methods: In this study, active components and action targets of Compound Huangbai Liquid were assessed via BATMAN-TCM. The target genes related to acne were extracted from GeneCards, DisGeNet and OMIM databases. Venn diagrams to predict potential targets for the treatment of acne. Protein-Protein interaction (PPI) analysis was proceeded through String database to obtain the core protein, and the protein interaction network was constructed by Cytoscape 3.9.1. Gene Ontology (Go) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed on Metascape platforms and bioinformatics.com.cn. TCM-compound-target-disease network and disease-target pathway network were constructed using Cytoscape to give the visual result. Finally, the results were further verified by establishing the mouse acne animal model.Results: This approach identified 165 active compounds, 1117 gene targets, 156 acne-related targets, and 34 potential target proteins for the treatment of acne with CHL. The biological processes were primarily related to cellular response to lipid, response to lipopolysaccharide, and regulation of secretion. The CHL was significantly associated with ten pathways including the Chagas disease and pathways in cancer. Animal experiments showed that CHL could significantly alleviate the levels of inflammatory factors and TLR4/NF-κB/p38 MAPK signaling pathway in acne.Conclusion: This study revealed the multiple active components, multiple targets, and multiple pathways of CHL in the treatment of acne, which provided a new perspective for the study of the mechanism of traditional Chinese medicine in the treatment of acne.Keywords: Compound Huangbai Liquid, acne, network pharmacology, inflammation